(untitled) (AIUB Journal of Science and Engineering (AJSE), 2023)
The main goal of this paper is to make a multifunctional robot along with a database management system named “MEDBOT”. That will reduce the problem of spreading any viral or infectious disease by maintaining social distance. A robot is designed and implemented will replace the ordinary system in the medical sector in a digital way with fewer life risks. Being a multifunctional robot, it can perform as a receptionist, entertainer, nurse, cleaner, and deliveryman. As a nurse, it will check a patient’s temperature, Heart Rate, Oxygen Saturation, and Heart condition in a contactless way. Furthermore, these vitals are easily stored in its database system. These vitals are broadcast on the device’s display and server, where the doctor can quickly monitor them in real-time. A mobile application-based remote-control system is equipped in this robot to control it remotely. Moreover, a disinfecting system and UV-C light are used for sterilizing purposes. The previously invented medical robot can perform one or two tasks, but a revolutionary change will come into the medical sector by making this robot. At last, it can be said that the ‘Medbot’ can reduce infectious disease, save time moreover digitalize the medical industry by doing these works. Finally, building a digital Bangladesh, it will work along with the medical sector as a warrior.